Efektivitas Kulit Buah Naga Merah (Hylocereus Polyrhizus) sebagai Antikolesterol - Lukman Hardia; Rizqi Fadil Nadila; Wahyuni Watora (Jurnal Sains & Kesehatan, 2026)
Hypercholesterolemia is a condition where blood cholesterol levels exceed normal limits, becoming a risk factor for coronary heart disease. The skin of the red dragon fruit (Hylocereus polyrhizus) contains flavonoids, betayanin, and dietary fiber that have the potential to lower cholesterol levels. This study aims to determine the effectiveness and optimal dose of red dragon fruit peel extract as a cholesterol lowering in white rats of the Wistar strain (Rattus novergicus) induced by high cholesterol feed. This study used the pretest and post-test with control group design method, with 25 mice divided into 5 groups: negative control, positive control (simvastatin 10mg) and treatment groups with extract doses of 15, 30, and 60 mg/kg BB. The results showed that red dragon fruit peel extract had the effectiveness of hypercholesterolemia with a dose of 60mg/kgBB providing the most optimal reducing effect. Conclusion: Ethanol extract of red dragon fruit peel can significantly lower cholesterol levels in rats with hypercholesterolemia.